Bacteriological threats in water sports: Challenges and Health Risks in the Lead - Up to Major Sporting Events - Kucharczyk, Natalia; Andrzejczak, Klara; Witkowski, Wiktor; Sternak, Agata; Gaweł-Dąbrowska, Dagmara (Quality in Sport, 2025)
Introduction: Water quality is a critical issue affecting human health, with contamination by pathogens leading to various diseases. Pathogens in water, often transmitted through the fecal-oral route, pose significant risks, causing gastrointestinal diseases and bacterial diarrhea. The World Health Organization (WHO) has set water quality standards for recreational use, and sports events like triathlons and the Olympics may involve waterborne infection risks. Additionally, athletes in water sports face health risks from physical exertion and environmental conditions, including exercise-induced bronchoconstriction, hypothermia, hyperthermia and swimming-induced pulmonary edema. Understanding these risks and implementing preventive measures are crucial for ensuring the safety and health of athletes and participants in water-based sports events. Purpose of the work: The purpose of this study is to review the impact and risks of pathogenic microorganisms found in water on the health and physical performance of athletes. Special attention is given to the organization of water sports competitions in the context of microbiological threats. Materials and methods: A comprehensive analysis of research articles available on PubMed, Google Scholar, Web of Science, Embase, and Scopus was conducted using search terms related to: "water sports", "microbiological hazards", "water pathogens", "water quality", "athletes" and "prevention." Results: Microbiological threats included in water expose participants in major sporting events to potential infection that can cause various health issues. To reduce these risks, water quality standards must be monitored, and actions should be taken when limits are exceeded. Event organizers must prioritize athlete safety, considering factors like weather and water quality, and involve public health authorities in decision-making. If health risks are identified, rescheduling or changing the event location should be considered.